Ganciclovir and Its Hemocompatible More Lipophilic Derivative Can Enhance the Apoptotic Effects of Methotrexate by Inhibiting Breast Cancer Resistance Protein (BCRP) - Markowicz-Piasecka, Magdalena; Huttunen, Johanna; Montaser, Ahmed; Adla, Santosh Kumar; Auriola, Seppo; Lehtonen, Marko; Huttunen, Kristiina M (International journal of molecular sciences, 2021)
Efflux transporters, namely ATP-binding cassette (ABC), are one of the primary reasons for cancer chemoresistance and the clinical failure of chemotherapy. Ganciclovir (GCV) is an antiviral agent used in herpes simplex virus thymidine kinase (HSV-TK) gene therapy. In this therapy, HSV-TK gene is delivered together with GCV into cancer cells to activate the phosphorylation process of GCV to active GCV-triphosphate, a DNA polymerase inhibitor. However, GCV interacts with efflux transporters that are responsible for the resistance of HSV-TK/GCV therapy. In the present study, it was explored whether GCV and its more lipophilic derivative (1) could inhibit effluxing of another chemotherapeutic, methotrexate (MTX), out of the human breast cancer cells. Firstly, it was found that the combination of GCV and MTX was more hemocompatible than the corresponding combination with compound 1. Secondly, both GCV and compound 1 enhanced the cellular accumulation of MTX in MCF-7 cells, the MTX exposure being 13-21 times greater compared to the MTX uptake alone. Subsequently, this also reduced the number of viable cells (41-56%) and increased the number of late apoptotic cells (46-55%). Moreover, both GCV and compound 1 were found to interact with breast cancer resistant protein (BCRP) more effectively than multidrug-resistant proteins (MRPs) in these cells. Since the expression of BCRP was higher in MCF-7 cells than in MDA-MB-231 cells, and the cellular uptake of GCV and compound 1 was smaller but increased in the presence of BCRP-selective inhibitor (Fumitremorgin C) in MCF-7 cells, we concluded that the improved apoptotic effects of higher MTX exposure were raised mainly from the inhibition of BCRP-mediated efflux of MTX. However, the effects of GCV and its derivatives on MTX metabolism and the quantitative expression of MTX metabolizing enzymes in various cancer cells need to be studied more thoroughly in the future.
Keywords: MFC-7 buňky; nádorové proteiny; Humans; ATP Binding Cassette Transporter, Subfamily G, Member 2; MCF-7/MDA-MB-231 human breast cancer cells; Multidrug Resistance-Associated Proteins; methotrexát; breast cancer resistant protein (BCRP); Female; Methotrexate; lidé; Human Umbilical Vein Endothelial Cells; apoptóza; Breast Neoplasms; ženské pohlaví; proteiny spojené s mnohočetnou rezistencí k lékům; antivirové látky; Ganciclovir; endoteliální buňky pupečníkové žíly (lidské); Antiviral Agents; nádorové buněčné linie; nádory prsu; multidrug resistance (MDR); Cell Line, Tumor; Neoplasm Proteins; ABC transportér z rodiny G, člen 2; methotrexate (MTX); ganciclovir (GCV); Apoptosis; ganciklovir; MCF-7 Cells